The SNM1A DNA repair nuclease - Baddock, HT; Yosaatmadja, Y; Newman, JA; Schofield, CJ; Gileadi, O; McHugh, PJ (Elsevier, 2020)
Unrepaired, or misrepaired, DNA damage can contribute to the pathogenesis of a number of conditions, or disease states; thus, DNA damage repair pathways, and the proteins within them, are required for the safeguarding of the genome. Human SNM1A is a 5′-to-3′ exonuclease that plays a role in multiple DNA damage repair processes. To date, most data suggest a role of SNM1A in primarily ICL repair: SNM1A deficient cells exhibit hypersensitivity to ICL-inducing agents (e.g. mitomycin C and cisplatin); and both in vivo and in vitro experiments demonstrate SNM1A and XPF-ERCC1 can function together in the ‘unhooking’ step of ICL repair. SNM1A further interacts with a number of other proteins that contribute to genome integrity outside canonical ICL repair (e.g. PCNA and CSB), and these may play a role in regulating SNM1As function, subcellular localisation, and post-translational modification state. These data also provide further insight into other DNA repair pathways to which SNM1A may contribute. This review aims to discuss all aspects of the exonuclease, SNM1A, and its contribution to DNA damage tolerance.